Training on the Application of Internet of Things (IoT)-Based Drying Fish Technology for Fishermen Groups in Bajo Village: Pelatihan Penerapan Teknologi Pengeringan Ikan Berbasis Internet of Things (IoT) Bagi Kelompok Nelayan Desa Bajo - Rasyid, Rusman; Lutfi, Salkin; Arilaha, Muhammad Asril; Hamsin, Hasanah; Taslim, Suratman (Yayasan Ahmar Cendekia Indonesia, 2024)
This community service activity aims to enhance the capacity of the fishing group in Bajo Village, Kayoa District, South Halmahera Regency, in applying more efficient and high-quality fish drying technology. Most fishermen in Bajo Village still use traditional sun-drying methods, which often face weather challenges and inconsistent drying results. The training was conducted in two stages: socialization and practice. In the socialization stage, fishermen were introduced to the importance of modern drying technology to improve the quality and marketability of dried fish products. During the practice stage, they were trained to use a internet of things (IoT) based drying fish device that can better control temperature and humidity. This training is expected to help fishermen improve the production of higher quality, hygienic, and competitive dried fish, thereby positively impacting the economic well-being of the Bajo Village community. Abstrak Kegiatan pengabdian ini bertujuan untuk meningkatkan kapasitas kelompok nelayan di Desa Bajo, Kecamatan Kayoa, Kabupaten Halmahera Selatan, dalam penerapan teknologi pengeringan ikan yang lebih efisien dan berkualitas. Sebagian besar nelayan di Desa Bajo masih menggunakan metode pengeringan tradisional yang bergantung pada sinar matahari, yang sering menghadapi kendala cuaca dan hasil pengeringan yang tidak konsisten. Pelatihan ini dilakukan dalam dua tahap, yaitu sosialisasi dan praktik. Pada tahap sosialisasi, nelayan diberikan pemahaman tentang pentingnya teknologi pengeringan modern untuk meningkatkan kualitas dan daya jual produk ikan kering. Pada tahap praktik, mereka dilatih menggunakan alat pengering ikan berbasis internet of things (IoT) yang dapat mengontrol suhu dan kelembapan secara lebih baik. Pelatihan ini diharapkan dapat membantu nelayan meningkatkan hasil produksi ikan kering yang lebih berkualitas, higienis, dan kompetitif di pasaran, serta memberikan dampak positif bagi kesejahteraan ekonomi masyarakat Desa Bajo.